Nickel-iron doped on granular activated carbon for efficient immobilization in biohydrogen production - Mohd Jamaludin, Nina Farhana; Abdullah, Luqman Chuah; Idrus, Syazwani; Engliman, Nurul Sakinah; Tan, Jian Ping; Jamali, Nur Syakina (Elsevier Ltd, 2024)
Nickel-iron doped granular activated carbon (GAC-N) was used to enhance immobilization in biohydrogen production. The effect of the sludge ratio to GAC-N, ranged 1:0.5–4, was studied. The optimum hydrogen yield (HY) of 1.64 ± 0.04 mol H2/mol sugar consumed and hydrogen production rate (HPR) of 45.67 ± 1.00 ml H2/L.h was achieved at a ratio of 1:1. Immobilization study was performed at 2 d HRT with a stable HY of 2.94 ± 0.16 mol H2/mol sugar consumed (HPR of 83.10 ± 4.61 ml H2/L.h), shorten biohydrogen production from 66 d to 26 d, incrementing HY by 57.30 %. The Monod model resulted in the optimum initial sugar, maximum specific growth rate, specific growth rate, and cell growth saturation coefficient at 20 g/L, 2.05 h−1, 1.98 h−1 and 6.96 g/L, respectively. The dominant bacteria identified was Thermoanaerobacterium spp. The GAC-N showed potential as a medium for immobilization to improve biohydrogen production.